Опыт эндодонтического лечения хронического периодонтита при наличии перфорации в области фуркаций корней (Эндодонтия Today, 2020)
Clinical evaluation of filling materials «Trioksident», «Pro Root» in relation to defects of hard tissues of the roots of teeth. Demonstration of the efficient use of osteoplastic material «Collapan» in the conservative treatment of diseases of the periapical tissue developed in consequence of failure of endodontic treatment.